Marshall cavendish cambridge primary maths pupil's book 1 - Soh, Christina; Soon, Spario (Marshall Cavendish Education Singapore, 2017)
The "Maths 1, Pupil's Book" introduces foundational math concepts for young learners. It covers topics like number recognition, basic addition and subtraction, simple shapes, and measurement. With engaging illustrations and clear explanations, it aims to build confidence and a positive attitude towards mathematics.